2010
DOI: 10.3208/sandf.50.281
|View full text |Cite
|
Sign up to set email alerts
|

Observed Behaviour of a Tunnel in Sand Subjected to Shear Deformation in a Centrifuge

Abstract: The paper describes observed behaviour of a model tunnel embedded in dry sand subjected to cyclic ground shear deformation in a centrifuge, as well as the behaviour of the model ground during shear deformation. Detailed data on earth pressures acting on the tunnel lining and the sectional forces of the lining are presented during ground shear deformation. The data suggest that the earth pressure at tunnel crown before ground shear deformation is smaller than the full overburden pressure probably due to the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Recently, Shibayama et al (2010) conducted centrifuge experiments on horseshoe-shaped tunnel models by applying cyclic shear deformations on the centrifuge models and measured earth pressures and bending moments around the lining. The tunnel models were statically sheared and therefore theˆndings do not include the eŠects of mass inertia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shibayama et al (2010) conducted centrifuge experiments on horseshoe-shaped tunnel models by applying cyclic shear deformations on the centrifuge models and measured earth pressures and bending moments around the lining. The tunnel models were statically sheared and therefore theˆndings do not include the eŠects of mass inertia.…”
Section: Introductionmentioning
confidence: 99%
“…e seismic response of rectangular tunnels has been a subject of in-depth research. A wide range of studies using centrifuge tests [2][3][4][5][6][7][8][9][10][11], shaking table tests [12][13][14][15][16][17][18][19], and numerical simulations [7,[20][21][22][23][24][25][26][27][28][29][30] have been performed. Previous studies revealed that there is a unique relationship between flexibility ratio (F) and the racking ratio (R), where F is the relative stiffness between the tunnel and the surrounding soil and R is defined as the ratio of the displacement of the tunnel and free-field soil.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed to investigate the seismic response of tunnels considering the dynamic soil-structure interaction, using a 1-g shaking table or centrifuge tests [ 14 , 16 26 ] and numerical analyses [ 4 , 14 15 , 27 38 ]. Most of these studies mainly focused on the tunnels installed in dry sands or liquefiable soils.…”
Section: Introductionmentioning
confidence: 99%